Reduced-Fat Response of Lactobacillus casei subsp. casei SY13 on a Time and Dose-Dependent Model - Jia, Zhenhu; Pang, Xiaoyang; Lv, Jiaping (Frontiers in Microbiology, 2018)
A reduced-fat effect of probiotics was primarily derived functionally rather than structurally, and we investigated the ultra-structural aspect of the gut mucosa in Syrian golden hamsters with high-fat diet by feeding with Lactobacillus casei subsp. casei SY13 (Lc SY13). 36 adult-male Syrian golden hamsters were randomly grouped into four; control group (G1), high-fat group (G2), high-dose group (G3), and low-dose group (G4). The G1 hamsters were fed a standard normal chow diet, while those in other groups were fed a high-fat chow diet for duration of 8 weeks. With the use of oral gavage, G1 hamsters were administered 1 mL of skim milk/hamster/day, while G3 and G4 hamsters were administered Lc SY13 at 4.1 × 1010 or 4.1 × 108 cells/hamster/day. At 14, 28, and 56 days consecutively, three golden hamsters from each group were sacrificed by carotid, taking blood from eyeball for quantitative detection of hamsters serum total cholesterol (TC), triacylglycerol (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). At 56 days, Taqman-MGB fluorescence probe was used for the quantitative detection of Lc SY13 in the intestinal mucosal, and their ileum was viewed using transmission electron microscopy (TEM). Screening of the ileum microvilli of the hamsters showed that at 56 days, G3 was significantly (P < 0.05) bigger than other groups while its serum TC, TG, and TDL decreased. Lc SY13 was detected in the intestines, and was significantly (P < 0.05) higher in the ileum of G3 than those of G4. In conclusion, Lc SY13 may play a remarkable reduced-fat response role by improving high-fat uptake as well as its metabolism and transport; most especially in G3. The reduced-fat response of the Lc SY13 differed in a time and dose-dependent manner. These findings indicated that probiotic strains of Lc SY13 can reduce fat level, thus suggesting its potential in ameliorating obesity-related diseases.